Harmonizing Society Through Islamic Education: An Analysis of Interactive Methods in Light of Tafsir Adhwa'ul Bayan - Ulum, Fira Miftahul; Sofiah, Sofiah; Kamto, Kamto; Rahmawati, Huzdaeni (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2025)
Raising the background of harmony in Islamic education, which is a crucial aspect in creating a peaceful and inclusive society. Social harmony in the context of education does not only focus on the transfer of knowledge, but also on the formation of positive social values ​​such as tolerance, empathy, and solidarity. The era of globalization that often threatens local cultural identity and increases social inequality, education has an important role as a builder of relationships between students who respect and understand differences. By using an interactive approach in the learning process, it aims to provide guidance for educators in creating a learning environment that supports social harmony. The method used in this study is library research. The results of this study are expected to contribute to the development of educational theory and more harmonious and inclusive learning practices. Thus, this study does not only focus on theoretical aspects, but also provides practical insights for educators in creating a learning environment that supports social harmony in the classroom.